The effect of milling parameters on synthesis of high yield boron nitride nanotube - Güler, S.H.; Aksoy, M.; Evin, E.; Güler, Ö. (National Institute of Optoelectronics, 2014)
In this study, high-yield Boron Nitride Nanotubes (BNNT) were synthesized by using the high energy ball milling method. Hexagonal Boron Nitride (h-BN) powder was used as starting powder and the powders were subjected to milling process for different milling rotations and different milling periods in a planetary ball mill (Fritsch Pulverisette 7 Premium Line). The powders obtained after providing the milling process, were annealed inside a tube furnace under NH3+Ar atmosphere at 1300°C for a period of 2 hours. In conclusion, BNNT's were produced by using this technique. The tubes produced have been examined by use of X-ray diffraction analysis (XRD), high resolution transmission electron microscopy (HR-TEM). © 2014, National Institute of Optoelectronics. All rights reserved.
Keywords: Boron nitride; High energy ball mill; Milling; Nanotube